The Effect of Giving Moringa Honey on Stress and Cortisol Levels in Pregnant Women in Maros Regency - Fitri Kumalasary, Veni Hadju, Werna Nontji, Andi Nilawati, Healthy Hidayanty, Sri Ramadany, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the effect of giving Moringa Honey on Stress and Cortisol Levels in pregnant women.This study used a Randomized Controlled Trial With Pre and Post Double Blind, where the parties involved in the study such as researchers and respondents did not know the difference between MH (Moringa Honey) and RH (Regular Honey) given to respondents. The research was carried out in the working area of the Turikale Health Center and Lau Health Center, Maros Regency, with stress and cortisol levels checking at the Turikale Health Center from February to April 2020. This study was carried out for two months (8 weeks). The sampling technique used was purposive sampling. The sample is 40 pregnant women. 20 samples were given MH intervention (Moringa Honey) and 20 samples were given 15 ml/day RH. In addition, pregnant women are given blood-enhancing tablets (Fe) which are consumed by the mother before going to bed. This study was conducted for 8 weeks, saliva samples were taken to determine cortisol levels. Saliva samples were examined using the Enzyme-linked immunorbent assay (ELISA) technique and then statistically analyzed using SPSS version 25. Most of the respondents aged between 20-25 years (22.5%), had more than 1 children (45.0%), earned around 1-3 million (42.5%). The results showed a decrease in stress in the MH group from 22.35 ± 5.21 to 18.80 ± 1.93 and the RH group from 19.35 ± 3.42 to 21.40 ± 2.79. The large difference in the changes in the two groups was seen to be significant with the value (p=0.001 vs p=0.022). There was a decrease in cortisol levels in the MH group from 1.86 ± 1.14 to 0.67 ± 0.63 and in the RH group from 1.20 ± 0.95 to 1.77 ± 1.02, the difference was significantly seen in the cortisol levels of the two groups with value (p=0.001 vs p=0.093).As a result, it can be inferred that giving MH (Moringa Honey) to pregnant women has a greater impact on lowering stress and cortisol levels.